Small Molecule Angiotensin II Type 2 Receptor (AT2R) Antagonists as Novel Analgesics for Neuropathic Pain: Comparative Pharmacokinetics, Radioligand Binding, and Efficacy in Rats. Issue 5 (14th March 2013) - Smith, Maree T.; Wyse, Bruce D.; Edwards, Stephen R.
Abstract: Objective: Neuropathic pain is an area of unmet clinical need. The objective of this study was to define the pharmacokinetics, oral bioavailability, and efficacy in rats of small molecule antagonists of the angiotensin II type 2 receptor (AT2 R) for the relief of neuropathic pain. Design and Methods: Adult male Sprague‐Dawley (SD) rats received single intravenous (1–10 mg/kg) or oral (5–10 mg/kg) bolus doses of EMA200, EMA300, EMA400 or EMA401 ( S ‐enantiomer of EMA400). Blood samples were collected immediately pre‐dose and at specified times over a 12‐ to 24‐hour post‐dosing period. Liquid chromatography tandem mass spectrometry was used to measure plasma drug concentrations. Efficacy was assessed in adult male SD rats with a unilateral chronic constriction injury (CCI) of the sciatic nerve. Results: After intravenous administration in rats, mean (±standard error of the mean) plasma clearance for EMA200, EMA300, EMA400, and EMA401 was 9.3, 6.1, 0.7, and 1.1 L/hour/kg, respectively. After oral dosing, the dose‐normalized systemic exposures of EMA400 and EMA401 were 20‐ to 30‐fold and 50‐ to 60‐fold higher than that for EMA300 and EMA200, respectively. The oral bioavailability of EMA400 and EMA401 was similar at ∼30%, whereas it was only 5.9% and 7.1% for EMA200 and EMA300, respectively. In CCI rats, single intraperitoneal bolus doses of EMA200, EMA300, and EMA400 evoked dose‐dependent pain relief. The pain relief potency rank order in CCI rats was EMA400 > EMA300 > EMA200 in agreement with the dose‐normalized systemic exposure rank order in SD rats. Conclusion: The small molecule AT2 R antagonist, EMA401, is in clinical development as a novel analgesic for the relief of neuropathic pain.